Optoproteomics elucidates the interactome of L-type amino acid transporter 3 (LAT3). Issue 38 (15th April 2021) - Wang, Liquan; Sun, Xiwen; Lu, Linjie; Marie, Arul; Carrel, Damien; Zhao, Shu; Mille, Clemence; Song, Qiong; Zhang, Yan; Ye, Shixin
Abstract : Membrane proteins are crucial for diverse biological processes. Optoproteomics technique enables the capture of proteome with unprecedented spatiotemporal resolution. Abstract : Membrane protein interactions are crucial for diverse biological processes. We report the application of genetic code expansion in combination with photo-crosslinking chemistry, as we termed "optoproteomics", to identify proteins interacting with the human L-type membrane amino acid transporter 3 (LAT3, also known as SLC43A1). The site-specifically incorporated photo-cross-linker p -azido- L -phenylalanine (AzF), which reacts with proteins in their proximity, enabled the capture of weak and transient partners of LAT3 in living cells. We identify 11 unique interacting proteins which are light-sensitive and 19 unique proteins that are site-specific, validating the approach and providing insights into the LAT3 protein–protein interaction network currently unavailable.